2018
DOI: 10.1002/joc.5848
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal prediction of high‐resolution temperature at 2‐m height over Mongolia during boreal winter using both coupled general circulation model and artificial neural network

Abstract: The hindcast data of Pusan National University coupled general circulation model (PNU CGCM), a participant model of the Asia‐Pacific Economic Cooperation Climate Center (APCC) Multi‐Model Ensemble Climate Prediction System, and August–October sea‐surface temperature (SST) in the northern Barents–Kara Sea (BKI) and the sea‐ice extent (SIE) in the Chukchi Sea (East Siberian Sea index [ESI]) are used for predicting 20 × 20‐km‐resolution anomalous surface air temperature at 2‐m height (aT2m) over Mongolia for bore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…A total of 40 ensemble members is large enough to minimize the initial conditions error and model uncertainty, considering the number of ensemble members produced by global institutes producing long‐term predictions using state‐of‐the‐art CGCMs. The details and performance of the model were introduced and studied by several authors (Ahn and Kim, 2014; Jo and Ahn, 2015; Bayasgalan and Ahn, 2018).…”
Section: Model and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 40 ensemble members is large enough to minimize the initial conditions error and model uncertainty, considering the number of ensemble members produced by global institutes producing long‐term predictions using state‐of‐the‐art CGCMs. The details and performance of the model were introduced and studied by several authors (Ahn and Kim, 2014; Jo and Ahn, 2015; Bayasgalan and Ahn, 2018).…”
Section: Model and Datamentioning
confidence: 99%
“…On both the interannual and interdecadal timescale, the western North Pacific subtropical High (WNPSH) can have a significant impact on the EA TC activities (Choi and Moon, 2012;Wang et al, 2013). Therefore, composite 1991, 1993, 2000, 20181980, 1981, 1983, 1984, 1995, 2003MEA 1994, 2000, 2005, 2006, 20181983, 1986, 1988, 1993, 1995, 1999, 2014SEA 1983, 1994, 19951982, 1999, 2004, 2010, 2014EEA 1991, 1994, 2000, 20181980, 1981, 1983, 1984, 1986, 1998, 2003, 2014 dipole pattern, which is analogous to the positive Pacific-Japan (PJ) teleconnection pattern. In this regard, previous studies showed that TCs land more frequently on NEA when the PJ pattern is positive than negative (Choi et al, 2010a;Kim et al, 2012).…”
Section: Relationship Between Ea Tc Landfalls and Atmospheric Circula...mentioning
confidence: 99%
“…Prediction models based on these methods have been built for winter temperature in China in operational forecasts (Chen et al, 2007;Ai et al, 2008;Jia et al, 2010;Wang et al, 2013b;Tan et al, 2017), as well as the prediction of extremely cold days Wang, 2016, 2017). Several new statistical approaches have also been developed for temperature forecasts, such as those based on artificial neural networks (Bayasgalan and Ahn, 2018) and spatiotemporal projection models (Vautard et al, 1999;Zhu and Li, 2017). However, the prediction skill of statistical models mainly relies on the statistical stability of the relationships between predictors and predictands, meaning there are considerable uncertainties in the prediction results if statistical relationships mutate (Li et al, 2013).…”
Section: Introductionmentioning
confidence: 99%